Low protein Z levels in patients with peripheral arterial disease - Sofi, Francesco; Cesari, Francesca; Pratesi, Giovanni; Cellai, Anna Paola; Pulli, Raffaele; Pratesi, Carlo; Gensini, Gian Franco; Abbate, Rosanna; Fedi, Sandra (Thrombosis and Haemostasis, 2007)
Conflicting findings regarding the association between protein Z and atherosclerotic disease have been reported. The aim of this case-control study was to evaluate the role of protein Z in a peripheral localization of atherosclerosis. We studied protein Z levels in 120 patients (102 male, 18 female; median age: 75 years) admitted to the Unit of Vascular Surgery of the University of Florence with a clinical manifestation of peripheral arterial disease (PAD), and in 360 healthy subjects selected to be comparable to the patients group in terms of age and gender. Protein Z levels were found to be significantly (p < 0.05) lower in PAD patients [1,594 (89–3,635) ng/ml] compared to the healthy control group [1,728 (300–3,736) ng/ml].A logistic regression analysis showed, at univariate analysis, a significantly increased risk of PAD in patients with low levels of protein Z (<5th percentile of our control group: < 601 ng/ml) (OR: 5.72, 95%CI 3.07–10.66; p < 0.0001). After adjustment for age, gender and traditional cardiovascular risk factors the association was confirmed (OR: 5.83, 95%CI 2.83–12.01; p < 0.0001). Moreover, a significant association between low protein Z levels and clinical severity of the disease, evaluated through Fontaine’s stages, was reported after adjustment for age, gender, and traditional cardiovascular risk factors (general linear model, p for trend: 0.03). In conclusion, our data shows an association between low protein Z levels and the occurrence of PAD. These findings provide evidence for the role of protein Z in the pathogenesis of the atherosclerotic disease.
Keywords: Protein Z; peripheral arterial disease; atherosclerosis